Physicochemical characterization of poly(tert-butyl acrylate-b-methyl methacrylate) prepared with atom transfer radical polymerization by inverse gas chromatography - Sakar, D; Erdogan, T; Cankurtaran, O; Hizal, G; Karaman, F; Tunca, U (ELSEVIER SCI LTD, 2006)
Poly(tert-butyl acrylate) (PtBuA) was synthesized by atom transfer radical polymerization (ATRP) using methyl-2-bromo propionate (MBP) as an initiator in bulk at 80 degrees C. The successive ATRP of methyl methacrylate in diphenyl ether at 80 degrees C using previously obtained PtBuA as a macroinitiator led to formation of poly(tert-butyl acrylate-b-methyl methacrylate) (poly(tBuA-b-MMA)). The synthesized macroinitiator and block copolymer have controlled molecular weight and low polydispersity (M-w/M-n < 1.2). The block copolymer was characterized by gel permeation chromatography (GPC) and H-1 NMR. The retention diagrams of poly (tBuA-b-MMA) for some aliphatic esters and aromatic hydrocarbons were obtained using inverse gas chromatography (IGC) technique. The glass transition temperatures, T(g)s of poly(tBuA-b-MMA) were determined by both differential scanning calorimeter (DSC) and IGC. It was observed that the block copolymer represents three TO at 50, 75 and 100 degrees C by IGC although it represents only one T, at 71 degrees C by DSC. After the column was quenched from 180 to 0 degrees C, the T-g at 100 degrees C shifted to 105 degrees C however others did not change. Specific retention volumes, V-g(0) and the thermodynamical polymer-solvent interaction parameters such as Flory-Huggins, chi(infinity)(12), equation-of-state, chi(*)(12) and effective exchange energy, X-eff were found for all studied solvents. Partial molar heat of sorption, Delta(H) over bar (1,sorp), partial molar heat of mixing, Delta(H) over bar (infinity)(1) and molar heat of vaporization, Delta H-v, were determined. In addition, the solubility parameter of the corresponding block copolymer, 62 was determined as 11.0 (cal/cm(3))(1/2) at 25 degrees C. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: poly(tert-butyl acrylate-b-methyl methacrylate); ATRP; inverse gas chromatography; THERMODYNAMIC INTERACTION PARAMETERS; SECONDARY TRANSITIONS; COPOLYMERS; Polymer Science